Reconsidering Subextraction: Evidence from Spanish - Bosque, Ignacio; Gallego, Ángel J. (Borealis – An International Journal of Hispanic Linguistics, 2014)
This paper argues that so-called subextraction (e.g., Whoi has John seen a picture of ti ?; cf. Corver 2006 for recent discussion) does not involve movement of a wh-phrase to a DP internal escape hatch position before reaching the CP layer. Instead, we claim that apparently subextracted wh-phrases are actually direct dependents of the verb after a process of reanalysis (or readjustment; cf. Chomsky 1977, Kayne 2002) applies. Our proposal rethinks an old (Bach & Horn 1976) idea, reframes it in modern terms and argues against the cyclic status of DPs (cf. Bruening 2009, Leu 2008, Ott 2008, and references therein), by leaning on new evidence from Spanish. The non-cyclic status of DPs is a fairly standard idea ever since clausal properties were assumed to hold for nominal domains (cf. Chomsky 1970, Brame 1982, Abney 1987, and much subsequent literature).